DELPHI TECHNIQUE: CONSENSUS OF ANATOMY CIRCULATORY SYSTEM CORE SYLLABUS FOR MEDICAL STUDENT - Siti Munawaroh; Farhah Millata Hanifa; Nanang Wiyono; Yunia Hastami; Nur Dewi Kartikasari; Bulan Kakanita Hermasari (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2018)
Background: Anatomy is a very important basic science in medical education. However, the advance of science and technology affected medical curriculum. One of the changes is the decreased time available for anatomy learning. Therefore, an anatomy lecturer needs to sort and choose from many existing anatomical materials to adjust with time allocation. The purpose of this study is to gain consensus on what minimum anatomical knowledge is for a physician candidate in order to practice safely. Method: This study was design in qualitative approach with two round Delphi Technique. Using purposive sampling method, the subjects of the study were 20 general-physicians in Indonesia. The questionnare was arranged based on anatomy text book and the research about anatomic core syllabus. The firts Delphi aimed to select the anatomical course material and additional course material. The second Delphi round intended to provide level range from 1-4. The consensus level established by researcher at 60% point.Results: There is not any additional topics in the first Delphi round. So the number of first and second round topics is 270 topics. The Delphi second round agree that anatomic core syllabus of circulation system is 110 of 270 topics. There are 30 topics of cor, 3 topics of pericardium, 10 topics of mediastinum, 37 topics of artery, 9 topics of vena, 9 topics of lymphathic system, 4 topics of postnatal circulation, 5 topics of prenatal circulation, and 3 topics of portal hepatic system.Conclusion: The anatomy core syllabus consists of 110 of the 270 anatomical circulatory system topics.